Myogenic nature of insect heartbeat and intestinal peristalsis, revealed by neuromuscular paralysis caused by the sting of a braconid wasp - Sláma, Karel; Lukáš, Jan (Journal of insect physiology, 2011)
Larvae of the greater waxmoth (Galleria mellonella) become paralysed by the venom of the braconid wasp (Habrobracon hebetor) a few minutes after intoxication. The profound neuromuscular paralysis, which may last for several weeks, includes all somatic muscles that are innervated through neuromuscular transmission. The peristaltic contractions of the heart and intestine, which are regulated by the depolarisation potentials of the myocardium or intestinal epithelial muscles, remain unaffected and fully functional. Heartbeat patterns and intestinal pulsations were monitored in the motionless, paralysed larvae by means of advanced electrocardiographic recording methods (contact thermography, pulse-light optocardiography). The records revealed more or less constant cardiac pulsations characterised by 20-25 systolic contractions per minute. The contractions were peristaltically propagated in the forward (anterograde) direction, with a more or less constant speed of 10mm per second (23-25°C). Additional electrocardiographic investigations on larvae immobilised by decapitation revealed the autonomic (brain independent) nature of heartbeat regulation. Sectioning performed in the middle of the heart (4th abdominal segment) seriously impaired the pacemaker rhythmicity and slowed down the rate of heartbeat in the anterior sections. By contrast, the functions of the posterior compartments of the disconnected heart remained unaffected. These results confirmed our previous conclusions about the existence of an autonomic, myogenic, pacemaker nodus in the terminal part of an insect heart. They show an analogy to the similar myogenic, sinoatrial or atrioventricular nodi regulating rhythmicity of the human heart. Peristaltic contractions of the intestine also represent a purely myogenic system, which is fully functional in larvae with complete neuromuscular paralysis. Unlike the constant anterograde direction of the heartbeat, intestinal peristaltic waves periodically reversed anterograde and retrograde directions. A possibility that the functional similarity between insect and human hearts may open new avenues in the field of comparative cardiology has been discussed.
Keywords: Animals; svaly; můry; Peristalsis; Intestines; Female; ženské pohlaví; Wasp Venoms; biologické hodiny; kousnutí a bodnutí hmyzem; vosí jedy; Moths; Electrocardiography; elektrokardiografie; Insect Bites and Stings; srdeční frekvence; střeva; Biological Clocks; peristaltika; nervový přenos; Synaptic Transmission; Muscles; Wasps; zvířata; sršňovití; Heart Rate